Static Treatment Modalities in Facial Paralysis: A Review - Ibrahim, Ahmed M. S.; Rabie, Amr N.; Kim, Peter S.; Medina, Miguel; Upton, Joseph; Lee, Bernard T.; Lin, Samuel J. (Journal of Reconstructive Microsurgery, 2013)
Introduction Facial nerve dysfunction can be attributed to several different causes. Several techniques have been developed to help treat the appearance and functional limitation of patients with sequelae of facial nerve dysfunction. There are options regarding static techniques of facial nerve injury treatment that range from facial musculature plication or shortening, fascial sling suspension via allograft or autograft, injectables and implants (ENDURAGen, AlloDerm, LifeCell, Bridgewater, New Jersey, USA) to techniques such as brow lift, open and endoscopic facelifts, and various eyelid surgeries with upper and lower lid procedures. In this review the various static facial nerve treatment modalities are discussed.Methods and Results A comprehensive review of the literature was performed detailing the most common static facial nerve treatment modalities and their known results and complications.Conclusions There are individual issues associated with facial palsy for which individual solutions must be carefully tailored. Despite the presence of many surgical options, the results of reconstruction are limited. With the rapid advancement of surgical techniques, approaches to the management of facial nerve dysfunction have expanded, helping surgeons to improve and utilize alternative techniques for the treatment of patients with acute and chronic facial paralysis.
Keywords: facial paralysis; static treatment; sling